If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y-9=10+8-y
We move all terms to the left:
2y-9-(10+8-y)=0
We add all the numbers together, and all the variables
2y-(-1y+18)-9=0
We get rid of parentheses
2y+1y-18-9=0
We add all the numbers together, and all the variables
3y-27=0
We move all terms containing y to the left, all other terms to the right
3y=27
y=27/3
y=9
| 5+-2x=3 | | –273=21n | | x2=8.2 | | -2-2n=7-3n | | 7(x-6)=2x-12 | | 4-8x=-76 | | 5(2x=3)=50 | | 10+2h+6=-8-h | | 10c-10=8c+10 | | 2(x5-3)=24 | | 2(3x+7)=-8 | | Y=270x | | 0,5x*(23-x)=60 | | 6x-10=43 | | 12p-9p+4p-2=5p | | -7p-7=-5p-2+5 | | -7-6n=-7n | | 9k+9=-7+5k | | 7-(x-6)=2x-12 | | -2x-3=2x-31 | | -7-9j=-8j | | 20²=3x² | | 3x-17=4x-18 | | 2x+13÷3=1 | | 5x–6=2x+6x= | | 51m=62 | | 2^3xx4^x-1=1/64 | | 1.6x+x=0.020 | | 1.6x=0.020-x | | (6z-9)÷3=5 | | 3(2x-4)=2(2x-3) | | a/3+6)=12 |